2018
DOI: 10.1155/2018/6309638
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic Causes and Epidemiological Characteristics of Patients with Intraocular Foreign Bodies: Retrospective Analysis of 1340 Cases over Ten Years

Abstract: Objective Patients with intraocular foreign bodies were retrospectively analyzed. Population characteristics, pathogenic factors, and the outcomes during the past ten years were discussed. Design Retrospective case series study. Method Medical records of 1340 patients hospitalized in Beijing Tongren Hospital from January 1, 2004, to December 31, 2013, were collected. Results Average age was 33.0 ± 13.8 (1–76) years old in 1340 patients. There were more males (1270, 94.8%) than females (70, 5.2%). Patients from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 25 publications
(33 reference statements)
2
17
1
1
Order By: Relevance
“…IOFBs occurrence in this population has been consistent over time. Previous reports investigating the characteristics and prognostic factors of IOFBs were largely retrospective [1, 79]. Our study suffers from the same limitation.…”
Section: Discussionmentioning
confidence: 90%
“…IOFBs occurrence in this population has been consistent over time. Previous reports investigating the characteristics and prognostic factors of IOFBs were largely retrospective [1, 79]. Our study suffers from the same limitation.…”
Section: Discussionmentioning
confidence: 90%
“…15 16 Li et al also reported that fireworks injury accounted for the majority of patients with IOFB aged 0-9 years in China. 17 Fireworks-related eye trauma mainly occurs in children, and is frequently severe and visually devastating. 15 18 The accidents involving fireworks diminished after children aged <18 years were prohibited from setting off fireworks in Finland.…”
Section: Discussionmentioning
confidence: 99%
“…Lin reported that fireworks (41.6%) and splashing of foreign body (49.1%) injuries dominate in retained patients with IOFB aged 0-9 and 10-19 years, respectively, similar to our findings. 17 Older children have increased security awareness and an expanded range of independent activities, resulting in different causes of injury. In addition, male patients were more prone to injury with fireworks, while females were more likely to be injured by plant branches, likely reflecting the different activities of males and females when they were injured.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies published for epidemiological characteristics and management outcomes of IOFBs are retrospective. 6,11,12 In our study design, data was also collected in retrospective manner. Majority of injuries (81.81%) occurred in male group.…”
Section: Discussionmentioning
confidence: 99%